Internationalization of SMES: business opportunities in Chile - Correia, João Filipe Amado (2017)
The main goal of this study is to identify the main business opportunities in Chile, legal advantages in the business perspective and entry strategies for small and medium sized enterprises (SMEs). The methodology used was qualitative, by conducting several interviews with chamber of commerce representative from Portugal in Chile and Chile in Portugal, several young entrepreneurs from different nations operating in Chile, the CEO of a Spanish company that decided to not internationalize to Chile and one large company that internationalized to Chile ten years ago as SME. The aim of these interviews was to understand the environment and process taken by SMEs and what kind of barriers and advantages did they find in this process. With both chamber of commerce, the author tried to identify macroeconomic factors that make the country interesting for SMEs. Finally, through the CEO of a Spanish SME specialized in IT services, the author tried to identify what made this company to analyze Chile as a possibility but not go further with the internationalization process. Research results find around ten business opportunities for SMEs, one program for international small business financing and development and the recommendation from the majority of the interviews in starting an internationalization process by developing a partnership or joint venture with a local partner or to internationalize through Startup Chile programs.